Dahanapura as a Source of Regency Work Clothing Ideas, Kediri - Sumargo, Oktya Anggarani; Purnomo, Arif Jati (Style : Journal of Fashion Design, 2024)
The Kediri or Panjalu kingdom was a kingdom located in East Java between 1042 and 1222. This kingdom was centered in Daha City. Daha is an abbreviation of Danapura, which means City of Fire. Dahanapura as a source of ideas for work attire for the Kediri Regency Tourism Office is a work inspired by the flame reliefs found in several places that are similar to each other. The aim of this work assignment is to create a flame batik motif and apply it to the work clothes of the Kediri Regency Tourism Office. The process of creating the work starts from the exploration stage, namely by observing several types of flames found on several inscriptions spread across Kediri, designing designs, alternative designs to be chosen as batik motifs to be applied to the work clothes of the Kediri district tourism office and also embodiment. The embodiment technique applied to the entire work uses the dyed dab batik technique using the synthetic dye Remasol. Starting from the pattern process, nyorek, batik, coloring, melorod, sewing to finishing. The results of creating this work are 6 works of work clothing with the titles Manuela, Desmond, Atalaya, Astama, Atlee, Amergyo. This design produces clothing works with Dahanapura motifs. By creating clothing works that use the Dahanapura motif, we can learn more about the inscriptions found in Kediri through batik media.